2014
DOI: 10.4239/wjd.v5.i6.917
|View full text |Cite
|
Sign up to set email alerts
|

Nonalcoholic steatohepatitis and insulin resistance in children

Abstract: Various pathological conditions can cause fatty liver in children. Nonalcoholic steatohepatitis (NASH) in children has been known since 1983. However, NASH diagnosed in childhood does not have a favorable outcome. The pathological characteristics of NASH are significantly different between children and adults. Nonalcoholic fatty liver disease (NAFLD)/NASH is accompanied by insulin resistance, which plays a pivotal role in its pathophysiology in both children and adults. In NASH, a "two-hit" model involving tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
15
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(25 citation statements)
references
References 46 publications
4
15
0
1
Order By: Relevance
“…Studies of patients with NAFLD have demonstrated that insulin resistance and pathologic HOMA might be predictors or at least associated with the development of a NAFLD (37, 38), which our study confirmed for our cohort. In addition, we found a significant association between NAFLD and elevated liver enzymes as well as a higher body fat proportion, which is in line with findings of patients without CP but with metabolic syndrome and NAFLD (39). The high rate of NAFLD we found in about 50% of CP patients with HI is higher than previous estimates and indicates that the monitoring of liver function is a critically important component in follow-up care of CP patients.…”
Section: Discussionsupporting
confidence: 89%
“…Studies of patients with NAFLD have demonstrated that insulin resistance and pathologic HOMA might be predictors or at least associated with the development of a NAFLD (37, 38), which our study confirmed for our cohort. In addition, we found a significant association between NAFLD and elevated liver enzymes as well as a higher body fat proportion, which is in line with findings of patients without CP but with metabolic syndrome and NAFLD (39). The high rate of NAFLD we found in about 50% of CP patients with HI is higher than previous estimates and indicates that the monitoring of liver function is a critically important component in follow-up care of CP patients.…”
Section: Discussionsupporting
confidence: 89%
“…Altogether, the observed differences between NASH in children and adults could be explained by the fact that secretion of CatD into the plasma is dependent on age-related changes of the lysosomes and therefore is dependent on accumulation of specific lipid species. In agreement, several studies indeed describe that the histological and pathological characteristics of NASH are age-dependent12131415. Further studies are warranted to precisely determine the contribution of lysosomes to NASH disease pathology in children and adults.…”
Section: Discussionsupporting
confidence: 63%
“…Recent studies have raised the concept that non-alcoholic fatty liver disease (NAFLD) in children and adults is distinct due to differences in the histological pattern in the liver as well as pathological characteristics of the disease12131415. Thus far, the relationship between plasma CatD and adult NASH has not been explored.…”
mentioning
confidence: 99%
“…For more simplified measurement of IR, fasting insulin and glucose, homeostasis model assessment of IR (HOMA-IR), insulin sensitivity indices-FFA (ISI-FFA), and quantitative insulin sensitivity check index (QUICKI) have been developed 91011. In addition, several previous studies analyzed the association between IR and NASH 12. A recent Korean study clearly showed higher body mass index (BMI), higher HOMA-IR values, and increased triglyceride (TG) ≥150 mg/dL associated with the occurrence of NAFLD in non-obese subjects 13…”
Section: Introductionmentioning
confidence: 99%